RELASI â€œBUDAK-TUANâ€ DALAM FILM FIFTY SHADES OF GREY - Sobhita Tryandari, Nyoman Ayu; Nugroho, Wahyu Budi; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI (SOROT), 2017)
This study examined the relation of slave-master between the main characters in Fifty Shades of Grey movie. The film was analyzed by using framing analysis technique Pan andKosicki. The result showed that literally Christian being the master while Anastasia as the slave. In addition of sexual intercourse, Christian also control of Anastasiaâ€™s life. The relation of the main characters could be reversed when it was examined through theory of social postmodern; slave-master discourse by Jacques Lacan. The Lacanâ€™s slave-master discourse emphasizes the more enjoyment with utterance â€œwho steals enjoyment greater than whoâ€. Anastasia got more enjoyment that Christian, since her pleasure was preferred by him such as in sexual intercourse. Anastasiaâ€™s desire was also fulfilled by Christian; even she got many sacrifices such as sleeping uniformly and asked him to out with a helicopter. Therefore, Anastasia was being the master and Christian as the slave in Lacan perspective since she got more enjoyment than him. Keywords: BDSM, slave-master relation, slave-master discourse